Pengaruh Eketivitas dan Efisiensi terhadap Kepercayaan dan Penggunaan Masyarakat Kota Jambi pada Transportasi Publik Trans Siginjai - Bayu Arinanto; Dimas Subekti; Arissy Jorgi Sutan; Riri Maria Fatriani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the influence of policy effectiveness and efficiency on public trust and the use of the Trans Siginjai public transportation system in Jambi City. The research background stems from the low public interest in using Trans Siginjai services since its operation in 2017, as reflected in the relatively small number of daily passengers. This research employs a quantitative method with an explanatory approach. Primary data were collected through a Likert-scale questionnaire distributed to 100 respondents determined using the Slovin formula, while secondary data were obtained from official documents and local media publications. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 4 software. The results show that both effectiveness and efficiency have a positive and significant effect on public trust, while trust significantly influences the level of Trans Siginjai usage. These findings emphasize that the success of public transportation policy depends not only on operational efficiency but also on the government’s ability to build public trust through consistent and high-quality service delivery.